Adverse Pregnancy Outcomes Among Individuals With and Without Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2): A Systematic Review and Meta-analysis. Issue 4 (April 2021) - Huntley, Benjamin J. F.; Mulder, Isabelle A.; Di Mascio, Daniele; Vintzileos, William S.; Vintzileos, Anthony M.; Berghella, Vincenzo; Chauhan, Suneet P.
Abstract : OBJECTIVE: To compare the risk of intrauterine fetal death (20 weeks of gestation or later) and neonatal death among individuals who tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) compared with those who tested negative for SARS-CoV-2 on admission for delivery. DATA SOURCES: MEDLINE, Ovid, EMBASE, Cumulative Index to Nursing and Allied Health, and Cochrane Library were searched from their inception until July 17, 2020. Hand search for additional articles continued through September 24, 2020. ClinicalTrials.gov was searched on October 21, 2020. METHODS OF STUDY SELECTION: The inclusion criteria were publications that compared at least 20 cases of both pregnant patients who tested positive for SARS-CoV-2 on admission to labor and delivery and those who tested negative. Exclusion criteria were publications with fewer than 20 individuals in either category or those lacking data on primary outcomes. A systematic search of the selected databases was performed, with co-primary outcomes being rates of intrauterine fetal death and neonatal death. Secondary outcomes included rates of maternal and neonatal adverse outcomes. TABULATION, INTEGRATION, AND RESULTS: Of the 941 articles and completed trials identified, six studies met criteria. Our analysis included 728 deliveries to patients who tested positive for SARS-CoV-2 and 3, 836 contemporaneous deliveries to patients who tested negative. Intrauterine fetal death occurred in 8 of 728 (1.1%) patients who tested positive and 44 of 3, 836 (1.1%) who tested negative ( P =.60). Neonatal death occurred in 0 of 432 (0.0%) patients who tested positive and 5 of 2, 400 (0.2%) who tested negative ( P =.90). Preterm birth occurred in 95 of 714 (13.3%) patients who tested positive and 446 of 3, 759 (11.9%) who tested negative ( P =.31). Maternal death occurred in 3 of 559 (0.5%) patients who tested positive and 8 of 3, 155 (0.3%) who tested negative ( P =.23). CONCLUSION: The incidences of intrauterine fetal death and neonatal death were similar among individuals who tested positive compared with negative for SARS-CoV-2 when admitted to labor and delivery. Other immediate outcomes of the newborns were also similar among those born to individuals who tested positive compared with negative for SARS-CoV-2. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD42020203475. Abstract : Individuals with and without severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) had similar rates of intrauterine fetal death, neonatal death, and Apgar score less than 7 at 5 minutes.